Mycobacterium bovis in the Dominican Republic, a study of detection, distribution and genomic variability - Reyes Santiago, Raysa Elena (2026)
Bovine tuberculosis (bTB) real prevalence in the Dominican Republic is unknown. Cattle are infected with Mycobacterium bovis and this has been confirmed by bacteriological culture, but very scarce information is available regarding M. bovis genotypes. Here, 56 M. bovis isolates obtained from tissue samples collected in different regions of the country were analyzed. Additionally, direct PCR was assayed on samples from tissue with tuberculosis like lesion and from milk. Molecular confirmation and genotyping were used to identify M. bovis in isolates, tissue and milk samples. Seven different spoligotypes were detected, and the major variety of isolates was found in the northern region of the country, where dairy production is frequent. The most prevalent spoligotype was SB0140. These results supports the presence and dissemination of bTB in important cattle production regions in the Dominican Republic. Insights regarding cattle production and mandatory bTB testing are discussed and considerations that might enhance bTB control in the Dominican Republic are presented.